Applied Research Note: Influence of dietary fat and crystalline amino acid inclusion on broiler diet formulation and subsequent pellet quality - K.M. Dunmire; J. Lee; K. Haydon; C.R. Stark; C.B. Paulk (Journal of Applied Poultry Research, 2024)
SUMMARY: A total of 3 broiler diets were pelleted to determine the effects of diet formulation on pellet quality. Dietary treatments consisted of corn and soybean meal-based control, the control with crystalline valine (Val), and the control with crystalline Val and isoleucine (Ile). As crystalline amino acids (AA) increased in the diets, corn concentrations increased as soybean meal and the fat source were removed to balance for nitrogen-corrected metabolizable energy (MEn). There were 3 replicates per treatment with time of processing as a blocking factor and treatment order randomized within each block. Cooled pellet samples were collected to determine pellet fines, standard pellet durability index (PDI), modified PDI, and Holmen NHP100. Pellet mill kW increased (P < 0.05) in pelleted Val + Ile diets compared to the control and Val diets. Pellet fines decreased (P < 0.01) and PDI increased (P < 0.01) as crystalline AA increased and added fat decreased in the diet. In conclusion, diets with increasing crystalline AA, Val, and Val + Ile, led to improved pellet quality which can be explained by the 0.4% or 0.6% reduction in added fat with increasing crystalline AA and balancing for MEn in the diet.